2020
DOI: 10.22158/jetr.v1n1p32
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of the Potential Impacts of Covid-19 on Tourism in Nigeria

Abstract: The outbreak and spread of covid-19 disease has resulted in countries of the world placing travel restrictions and closure of their borders to movements to and from other countries. The tourism industry is one of the sectors that would be greatly affected. Data for the study was generated from desk review of secondary materials, online blogs and interview through social media chat. Findings of the study reveal that the outbreak and spread of covid-19 disease led to rapid shutdowns in cities and states across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…As the budgets and guest houses have fewer employees, these facilities are able to manage the few employees during the pandemic by retaining their staff as compared to that of the bigger hotels. This present study confirmed that Oruonye and Ahmed (2020) in Nigeria highlighted that many hotels have already closed down because of low patronage and inability to meet up with the payment of worker’s salary and electricity and water bills. Many had to cut down on their workforce, while others slash their workers’ salaries by 50%.…”
Section: Findings and Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…As the budgets and guest houses have fewer employees, these facilities are able to manage the few employees during the pandemic by retaining their staff as compared to that of the bigger hotels. This present study confirmed that Oruonye and Ahmed (2020) in Nigeria highlighted that many hotels have already closed down because of low patronage and inability to meet up with the payment of worker’s salary and electricity and water bills. Many had to cut down on their workforce, while others slash their workers’ salaries by 50%.…”
Section: Findings and Analysissupporting
confidence: 87%
“…COVID-19, with its dramatic drop in sales and income, will make it extremely difficult for many hospitality firms to continue paying their employees, resulting in job loss. A study in Nigeria by Oruonye and Ahmed (2020) reveals that several hotels are closed because of reduced demand and inability to pay employee salaries.…”
Section: Covid-19 Effect On Hotels In Africamentioning
confidence: 99%
“…Regarding the demographic factors, Acemoglu et al ( 2020) considers structural differences in infections for distinct age groups that affect lockdown policies and economic costs (Çakmaklı et al, 2020). In general, the various economic areas affected by the outbreak of COVID-19 includes; Global disaster (Gupta, 2020), tourism industry (Oruonye & Ahmed, 2020), supply chain disruptions (Oruonye & Ahmed, 2020; Tang, Gaoshan, & Ahonsi, 2020) food insecurity (Cosgrove, 2020), shortage of raw materials (Tang et al, 2020), drop in productivity and efficiency (Raja, Lennes, & Biddinger, 2020). These economic difficulties lead to loss of employment which further affects food security.…”
Section: Discussionmentioning
confidence: 99%
“…It is projected that the spread of the disease will have serious humanitarian challenges to the countries of the world and especially Africa and Nigeria in particular. Economically, the effects have already been felt as demand for Africa's raw materials and commodities in global market has declined and Africa's access to industrial components and manufactured goods from other regions of the world has been hampered [22].…”
Section: Some Policy Suggestion To Mitigate the Economic Impacts Of Covid-19mentioning
confidence: 99%
“…There are several channels through which the COVID-19 outbreak will affect economic activity in developing countries, the rest of developing Asia, and the world. These include a sharp but temporary decline in domestic consumption and other outbreak-affected economies, and possibly investment if the outbreak affects views on future business activity; declines in tourism [22] and business travel; spillovers of weaker demand to other sectors and economies through trade and production linkages; supply-side disruptions to production and trade (which are distinct from demand-side shocks spilling over through trade and production linkages); and effects on health such as increased disease and mortality as well as shifts in health care spending. As each of these are taken in turn [2].…”
Section: Introductionmentioning
confidence: 99%